Enhancing EFL Students’ Reading Comprehension and Motivation through the SQ3R Method: A Classroom Action Research Study - Indri Nurhasanah Suarno; Tahrun; Masagus Firdaus (FOSTER: Journal of English Language Teaching, 2025)
This study investigates the implementation of the SQ3R (Survey, Question, Read, Recite, Review) method in a ninth-grade classroom at SMP Negeri 4 Rambang Niru, aiming to enhance both reading comprehension and student motivation. A total of 28 students participated in this classroom action research project, which spanned an academic semester. To evaluate the effectiveness of the SQ3R methodology, the research employed test cycle implementation for reading comprehension assessments, alongside a motivation questionnaire adapted from the Attitude Motivation Test Battery (AMTB). This comprehensive approach allowed for a detailed examination of the interconnected variables of motivation and comprehension. The results indicated a significant improvement in students' reading comprehension abilities and a noticeable increase in motivation levels, with 85% of participants reporting enhanced interest in reading tasks. Furthermore, the findings illustrated that utilizing a structured approach like SQ3R not only deepened student engagement but also empowered learners to take ownership of their educational experiences. This aligns with existing literature underscoring the correlation between motivation and reading outcomes and suggests that motivated students generally display improved comprehension skills. The implications of this research emphasize the necessity for educators to integrate motivational techniques into reading instruction and suggest opportunities for further research across diverse educational contexts. Future studies may explore the long-term impacts of the SQ3R method on various age groups or demographic profiles, contributing to a broader understanding of its effectiveness in different learning environments.